Electronic Purses in Euroland: Why do Penetration and Usage Rates differ? - Leo Van Hove (SUERF - The European Money and Finance Forum, 2004)
This paper documents the recent performance of European electronic purses. It presents data on 16 such schemes, and compares their penetration and usage rates. These rates are shown to differ substantially. A number of schemes are doing increasingly well and in all probability are here to stay. These schemes have also received a boost from the introduction of the euro. But a number of other schemes are making little or no headway. Some have even experienced a relapse and appear to be on the verge of disappearance. The paper tries to identify explanations for these disparate fates.
Keywords: E41; 330; Electronic money; payment systems; electronic purses; E-purses; demand for money; Elektronisches Geld; Chipkarte; Bargeldloser Zahlungsverkehr; Euro; EU-Staaten